2022
DOI: 10.1038/s41598-022-07657-8
|View full text |Cite
|
Sign up to set email alerts
|

Zoomed out: digital media use and depersonalization experiences during the COVID-19 lockdown

Abstract: Depersonalisation is a common dissociative experience characterised by distressing feelings of being detached or ‘estranged’ from one’s self and body and/or the world. The COVID-19 pandemic forcing millions of people to socially distance themselves from others and to change their lifestyle habits. We have conducted an online study of 622 participants worldwide to investigate the relationship between digital media-based activities, distal social interactions and peoples’ sense of self during the lockdown as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
0
12
0
1
Order By: Relevance
“…By contrast, more basic and ‘humble’, body- and movement-based abilities (e.g., manual workings, physical exercise, etc.) will be positively correlated with low levels of depersonalisation ( Ciaunica et al, 2022b ). Again, experimental tests of these ideas will have to be carefully assessed in order to exclude potential confounding effects of demand characteristics ( Lush, Botan, & Scott, 2020 ).…”
Section: The Split ‘I’: Linking Mechanisms and Phenomenology Of Alter...mentioning
confidence: 99%
“…By contrast, more basic and ‘humble’, body- and movement-based abilities (e.g., manual workings, physical exercise, etc.) will be positively correlated with low levels of depersonalisation ( Ciaunica et al, 2022b ). Again, experimental tests of these ideas will have to be carefully assessed in order to exclude potential confounding effects of demand characteristics ( Lush, Botan, & Scott, 2020 ).…”
Section: The Split ‘I’: Linking Mechanisms and Phenomenology Of Alter...mentioning
confidence: 99%
“…Higher deindividualization experiences lead to increased negative emotional interactions. Overly sedentary, digital lifestyle habits may induce an individual's sense of disconnection from the body, self, and world (Ciaunica et al, 2022). Consequently, this study suggests that the communication of negative emotions may be influenced by the variability of individuals' self-presentation on social media and multiple elements of group relationships, social events, and emotional characteristics.…”
Section: Negative Emotional Communicationmentioning
confidence: 86%
“…Recent studies suggest a distribution of such experiences also in the general population with varying degrees (Yang et al 2022) and transient DP has been reported for 34 -70% in the general population (Hunter et al 2017). People with DP report experiencing a blurring of self-other-boundaries, difficulties in relating to others, and altered somatosensory perceptions (Salami et al 2022;Ciaunica et al 2022).…”
Section: Introduction: (Dis)embodied Selfhood and Attitudes Towards R...mentioning
confidence: 99%
“…Humans are highly social beings, constantly interacting with others from early life (Rochat 2004, Hamilton 2020Ciaunica et al 2022). In recent years, technological advances made possible novel types of interactions between humans and artificial embodied systems, such as robots, opening new challenges on our current understanding of what human sociality is ( Hortensius & Cross, 2018;van de Poel et al, 2023).…”
Section: Introduction: (Dis)embodied Selfhood and Attitudes Towards R...mentioning
confidence: 99%
See 1 more Smart Citation